Imaging of iron - Dusek, Petr; Dezortova, Monika; Wuerfel, Jens (International review of neurobiology, 2013)
Magnetic resonance imaging (MRI) enables a noninvasive in vivo quantification of iron in various organs. Several techniques have been developed that detect signal alterations derived mainly from the magnetic properties of ferritin and hemosiderin, the major iron storage compounds. High magnetic susceptibility of ferritin shortens the transversal relaxation time of nearby water protons and thus induces a focal signal extinction of iron-rich areas in T2-weighted (T2w) MRI. T2w tissue contrast is additionally influenced by other factors such as water content, myelin density, and the presence of other metals. Therefore, more specific methods are needed with higher specificity to iron. These in vivo techniques can be divided into three groups: relaxometry, magnetic field correlation imaging and phase-based contrast covering susceptibility-weighted imaging, and quantitative susceptibility mapping. The differential diagnosis of various neurological disorders is aided by characteristic patterns of iron depositions. Reliable estimates of cerebral tissue iron concentration are equally important in studying physiological age-related as well as pathological conditions in neurodegenerative, neuroinflammatory, and vascular diseases. In the future, monitoring changes in iron storage and content may serve as sensitive biomarker for diagnosis as well as treatment monitoring.
Keywords: Chelating agents; Nerve Degeneration; degenerace nervu; Magnetic Resonance Imaging; Neurodegeneration; Neurodegenerative Diseases; lidé; Relaxometry; MRI; NBIA; SWI; magnetická rezonanční tomografie; Brain; Iron; železo; mozek; neurodegenerativní nemoci; Humans